2022
DOI: 10.2174/1570159x19666210517150418
|View full text |Cite
|
Sign up to set email alerts
|

Off-label Uses of Selective Serotonin Reuptake Inhibitors (SSRIs)

Abstract: : Psychiatric drugs have primacy for off-label prescribing. Among those, selective serotonin reuptake inhibitors (SSRIs) are extremely versatile and, therefore, widely prescribed. Moreover, they are commonly considered as having a better safety profile compared to other antidepressants. For these reasons, when it comes to off-label prescribing, SSRIs rank among the top positions. In this review, we present the state of the art of off-label applications of selective serotonin reuptake inhibitors, ranging from m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 182 publications
0
19
0
Order By: Relevance
“…This may be partly due to the propensity for clinicians to use antidepressants, predominately SSRIs, as an established treatment in alternative psychological conditions or for use in off-label conditions where there is a limited evidence base. 58 60 …”
Section: Discussionmentioning
confidence: 99%
“…This may be partly due to the propensity for clinicians to use antidepressants, predominately SSRIs, as an established treatment in alternative psychological conditions or for use in off-label conditions where there is a limited evidence base. 58 60 …”
Section: Discussionmentioning
confidence: 99%
“…14 What's more, dapoxetine can take effect in a short time and obviously extend IELT in men with PE. 36 In this study, dapoxetine had significant effects on the ejaculatory behavior of rapid rats. The frequency of ejaculation in rapid rats with acute administration of dapoxetine was decreased, while the ejaculation latency was significantly prolonged.…”
Section: Discussionmentioning
confidence: 96%
“…Unlike classical SSRIs, dapoxetine is absorbed and removed rapidly in the body 14 . What's more, dapoxetine can take effect in a short time and obviously extend IELT in men with PE 36 . In this study, dapoxetine had significant effects on the ejaculatory behavior of rapid rats.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the preferred treatment for PE is SSRIs (Sathianathen et al, 2021). Paroxetine is the common SSRIs and can significantly increase the content of 5‐hydroxytryptamine (5‐HT) in postsynaptic membrane receptors, thereby playing a key role in delaying ejaculation (Jannini et al, 2021). Although it was not FDA approved for use in PE, the comparison of paroxetine with other regimens has been investigated in a number of high‐quality randomized controlled trials (RCTs) and showed comparable therapeutic effects (Gameel et al, 2013; Hamidi‐Madani et al, 2018; Salonia et al, 2002).…”
Section: Introductionmentioning
confidence: 99%